KETIDAKADILAN GENDER TERHADAP ISTERI PETANI DI KEC. PORTIBI KAB. PALUTA - Santi Marito Hasibuan (Jurnal Kajian Gender dan Anak, 2019)
This study aims to identify forms of gender injustice against farmers' wives in Portibi District, Paluta Regency. The method used in this study is a qualitative-phenomenological method, while data collection is done by interview and observation methods. The results of this study concluded that the wife of a farmer in Portibi District experienced gender inequality. Forms of injustice experienced by farmers' wives occur in refroductive work, subordination, double burden, marginalization and domestic violence.Kata Kunci : Ketidakadilan, gender, isteri petani